IMPLEMENTASI UNDANG-UNDANG NO 28 TAHUN 2004 PERUBAHAN ATAS UNDANG-UNDANG NO 16 TAHUN 2001 TENTANG YAYASAN - Sukirman Sukirman (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Government to guarantee certainty and orderliness of law, hence there is effort to purify again deviation to purpose and objectives of is forming of institution. Therefore institution to purposes and objectives of is forming of institution. Therefore institution old ones its existence remain to confess as legal body, on condition that have been registered in district court and announced in Addition Official Gazette Republic Of Indonesia and also have permission conduct activity of related/relevant institution. That way also institution as company which is legal body and domicile in unity state republic of Indonesia region, hence is obliged to be registered at list company. Beside that institution as taxpayer and can conduct commercial business unit, hence institution is obliged to pay for lease of income. This obligation will vanish if institution obtain;get earnings of contribution, donation, and communal ownership. Kata kunci : daftar perusahaan, pajak pendapatan